Edukasi Gizi dan Pencegahan Stunting di Desa Buar, Manggarai, Flores, NTT - Niman, Erna Mena; Darong, Hieronimus Canggung; Wea, Lidwina Dewiyanti; Jandu, Inosensius Harmin (Universitas Prof. Dr. Moestopo (Beragama), 2026)
Stunting remains a serious public health issue in Indonesia, particularly in East Nusa Tenggara (NTT), which has a higher prevalence compared to other regions. This community service activity was carried out in Buar Village, North Rahong Subdistrict, Manggarai Regency by a team from Santu Paulus Ruteng Catholic University. The implementation methods included collecting stunting data from the health department, conducting interviews with the village head, an initial assessment of community understanding, educational outreach, mentoring, and a final evaluation. Initial assessments showed that only 30% of the community understood issues related to nutrition and stunting, primarily those with higher education levels. After educational sessions led by four expert speakers and interactive mentoring, community understanding significantly increased to 75%. This activity demonstrates that community-based education is effective in raising public nutrition awareness. The sustainability of stunting prevention efforts requires cross-sector collaboration among the government, community members, traditional leaders, and educational institutions so that knowledge change can be translated into real, everyday behaviors.